2020
DOI: 10.3390/s20113213
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Wins, Losses and Attributes’ Sensitivities in the Soccer World Cup 2018 Using Neural Network Analysis

Abstract: Predicting the results of soccer competitions and the contributions of match attributes, in particular, has gained popularity in recent years. Big data processing obtained from different sensors, cameras and analysis systems needs modern tools that can provide a deep understanding of the relationship between this huge amount of data produced by sensors and cameras, both linear and non-linear data. Using data mining tools does not appear sufficient to provide a deep understanding of the relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 53 publications
(66 reference statements)
0
3
1
Order By: Relevance
“…In our study however, the aim was to identify the strongest predictive variables, so instead of a division between historic and future games, a cross-validation approach was used to evaluate model performance. The prediction accuracy was considerably higher compared to a similar study conducted by [28], who reported classification accuracies of 72.7% and 83.3% when predicting respectively losing and winning in professional soccer using artificial neural networks. A classification accuracy of amply 89% can be considered as high, as it has been shown that chance plays a major role in goal-scoring [29].…”
Section: Discussioncontrasting
confidence: 68%
“…In our study however, the aim was to identify the strongest predictive variables, so instead of a division between historic and future games, a cross-validation approach was used to evaluate model performance. The prediction accuracy was considerably higher compared to a similar study conducted by [28], who reported classification accuracies of 72.7% and 83.3% when predicting respectively losing and winning in professional soccer using artificial neural networks. A classification accuracy of amply 89% can be considered as high, as it has been shown that chance plays a major role in goal-scoring [29].…”
Section: Discussioncontrasting
confidence: 68%
“…These systems are able to evaluate the activities of players successfully [79] such as the distance covered by players, shot detection [80,81], the number of sprints, player's position, and their movements [82,83], the player's relative position concerning other players, possession [84] of the soccer ball and motion/gesture recognition of the referee [85], predicting player trajectories for shot situations [86]. The generated data can be used to evaluate individual player performance, occlusion handling [21] by the detecting position of the player [87], action recognition [88], predicting and classifying the passes [89][90][91], key event extraction [92][93][94][95][96][97][98][99][100][101], tactical performance of the team [102][103][104][105][106], and analyzing the team's tactics based on the team formation [107][108][109], along with generating highlights [110][111][112][113]. Table 3 summarizes various proposed methodologies to resolve various challenging tasks in soccer with their limitations.…”
Section: Soccermentioning
confidence: 99%
“…Hassan et al applied CNN to predict the winning or losing and attribute sensitivity of the 2018 World Cup. They thought that sports scientists could use a new neural network model based on radial function to adjust training, tactics and confrontation analysis to improve their performance 16 .…”
Section: Introductionmentioning
confidence: 99%